?EFFECT OF RATES AND METHODS OF NITROGEN APPLICATION ON THE GRAIN YIELD AND NITROGEN UPTAKE OF WETLAND RICE - CHOUDHURY, A.T.M.A.; BHUIYAN, N.I (Biological Sciences - PJSIR, 1994)
Two field experiments were carried out during dry and wet seasons of 1991 to study the effect of three application methods and four rates of nitrogen fertilization on yield and N nutrition of wetland rice using randomised complete block design. The test varieties wereBR3 and BRIl during dry and wet seasons respectively. Regarding grain yield, urea supergranule (USG) point placement was significantly superior to prilled urea (PU) broadcasting at all the levels of applied N in both the cases of BR3 and BRl1, whereas PU injection was significantly superior to PU broadcasting only at the highest N rate. Agronomic efficiency, total N uptake and apparent recovery of added N was the highest with USG point placement followed by PU injection and was lowest with PU broadcasting in both the seasons. Agronomic efficiency and apparent recovery of added N decreased gradually with increasing N rates irrespective of fertilizer application methods in both the cases ofBR3 and BRIl.